Adverse Effects of Selected Markers on the Metabolic and Endocrine Profiles of Obese Women With and Without PCOS - Daghestani, Mazin H.; Daghestani, Maha H.; Warsy, Arjumand; El-Ansary, Afaf; Omair, Mohammed A.; Omair, Maha A.; Hassen, Lena M.; Alhumaidhi, Eman MH.; Al Qahtani, Bashaer; Harrath, Abdel Halim (Frontiers in Endocrinology, 2021)
This study investigated the influence of obesity, with and without PCOS, on the levels of kisspeptin, Vit D, and VEGF and to explore the relationship between these parameters and endocrine and metabolic variables. The study group included 126 obese Saudi females, 63 were suffering from PCOS while the rest were normo-ovulatory obese women. In the obese PCOS, VEGF was four times higher than in the obese, while kisspeptin and Vit D did not differ. A significant elevation was recorded in the waist/hip (WHR), cholesterol, LDL-C, fasting glucose, LH, LH/FSH ratio, E2, and testosterone, while hip circumference, leptin, progesterone, and SHBG were lower in the obese PCOS subjects. BMI, HDL-C, ghrelin, insulin, and FSH levels did not differ between the two groups. The obese PCOS had the same level of insulin resistance as the non-PCOS group, as judged by QUICK Index. Correlation studies showed a significant negative correlation between kisspeptin and glucose and LH levels, and a positive correlation with LH/FSH ratio in obese PCOS while in the non-PCOS obese, the kisspeptin correlated positively only with glucose. VEGF negatively correlated with FSH and positively with LH/FSH ratio in the non-PCOS obese but this was lost in the obese PCOS. PCOS had no effect on the correlation between Vit D and all studied parameters. Multiple regression analysis showed triglyceride as predictor variable for kisspeptin as a dependent variable, while, leptin is a predictor variable for VEGF as a dependent variable. ROC studies showed the highest sensitivity and specificity for VEGF (AOC=1.00), followed by LH/FSH ratio (AOC=0.979). In conclusion, our study shows that PCOS results in significant elevation of VEGF in obese females, while kisspeptin and Vit D levels are not affected. It also leads to elevation in several of the lipid and hormonal abnormalities in the obese females. In addition, PCOS influences relationship between Kisspeptin and VEGF and some parameters such as glucose, LH or FSH and LH/FSH ratio in obese females, but does not affect Vit D relationship with other parameter.